The Effect of Carbon Emission Disclosure and Environmental Costs On Financial Performance with Environmental Performance as a Moderating Factor - Fauziah, Dewi Ainun; Puspita, Dewi Ayu (Universitas Negeri Yogyakarta, 2024)
ABSTRACTThe research was conducted to test the disclosure of carbon emissions and environmental costs and their impact on environmental costs, with financial performance as its moderation. The study used an explanatory research method with 72 manufacturing companies listed in the BEI during the period 2018–2022 as a sample. The sampling technique used is purposive sampling. The data sources used are secondary data, namely sustainability reports and annual company reports of samples analyzed using moderate regression analysis (MRA). According to research, disclosure of carbon emissions has no effect on financial performance; environmental costs have an impact on financial performance; carbon disclosures have an impact on financial performance by moderating environmental performance; and carbon disclosure has an impact on financial performance by moderating environmental performance.Keywords: Carbon Emissions, Environmental Costs, Financial Performance, Environmental Performance, ManufacturedABSTRAKPenelitian ini dilakukan guna menguji pengungkapan emisi karbon dan biaya lingkungan berdampak pada biaya lingkungan dengan kinerja keuangan sebagai moderasinya. Penelitian ini menggunakan metode explanatory research dengan 72 perusahaan manufaktur yang terdaftar di BEI selama periode 2018-2022 sebagai sampel. Teknik pengambilan sampel yang dipakai menggunakan purposive sampling. Sourch data yang digunakan adalah data sekunder yakni laporan keberlanjutan dan annual report perusahaan sampel yang dianalisis menggunakan Moderated Regression Analysis (MRA). Penelitian menunjukkan bahwa pengungkapan emisi karbon tidak mempengaruhi kinerja keuangan; biaya lingkungan mempengaruhi kinerja keuangan; pengungkapan emisi karbon mempengaruhi kinerja keuangan dengan dimoderasi kinerja lingkungan; dan pengungkapan emisi karbon mempengaruhi kinerja keuangan dengan dimoderasi kinerja lingkungan.Kata kunci: Emisi Karbon, Biaya Lingkungan, Kinerja Keuangan, Kinerja Lingkungan, Manufaktur